Numerical analysis of absorber tube shapes in PCM-integrated parabolic trough solar collectors - Kumar, Binit; Awasthi, Abhishek; Lee, Jungho; Jeon, Yongseok (Case Studies in Thermal Engineering, 2025)
This study examines the impact of absorber tube geometry on the thermal performance of parabolic trough collectors (PTCs) integrated with phase change materials (PCMs). Addressing a research gap, it compares circular, elliptical, and pear-shaped absorber tubes using solar salt as PCM and water as the heat transfer fluid. The study aims to identify optimal designs for improving thermal efficiency and system scalability in solar energy applications. Results showed that the pear-shaped tube outperformed the circular design, achieving 6–8 °C higher outlet temperatures, a 7 % increase in instantaneous power, and a 15-min longer heat retention time. While the elliptical tube exhibited lower overall performance, its horizontal orientation enhanced power output by 5 % compared to the vertical orientation. These findings underscore the critical role of absorber tube geometry in optimizing PCM-integrated PTCs. The pear-shaped absorber tube, with its superior heat flux concentration and heat transfer efficiency, demonstrated significant potential for enhancing system performance. Its optimized geometry makes it a promising candidate for scalable and efficient solar energy solutions in industrial and domestic applications, offering advancements in sustainable energy utilization.
Keywords: Absorber shape; Absorber tubes; Energy; In-phase; Latent heat storage; Parabolic trough collectors; Parabolic trough solar collectors; Phase Change; Tube geometry; Tube shape; Absorber shapes; Latent heat storage; Parabolic trough collector; Phase change material; Solar energy